Virtual worlds and criminality - Cornelius, Kai; Hermann, Dieter (Springer, 2011)
Virtual worlds as a regulatory challenge : a user perspective / Christoph Klimmt -- Crime potential of metaverses / Christian Laue -- Is virtual violence a morally problematic behavior? / Tilo Hartmann -- Media violence and criminality / Dieter Hermann -- Internet dependency : symptoms, diagnosis and therapy / Bert Theodor teWildt -- Conflict resolution in virtual worlds : general characteristics and the 2009 Dutch convictions on virtual theft / Arno R. Lodder -- Responsibility under criminal law in virtual worlds / Kai Cornelius
Literaturangaben
Keywords: Aufsatzsammlung; Konferenzschrift -- 2011 -- Heidelberg; Stoffungebundene Sucht; Internet; Gewaltdarstellung; Virtuelle Realität